Participation of lysine-sensitive aspartokinase in threonine production by S-2-aminoethyl cysteine-resistant mutants of Serratia marcescens. - Komatsubara, S (1979)
S-2-Aminoethyl cysteine (AEC) reduced both growth rate and final growth level of Serratia marcescens Sr41. The growth inhibition was completely reversed by lysine. AEC inhibited the activity of lysine-sensitive aspartokinase to a lesser extent than lysine. The AEC addition to the medium lowered not only the level of lysine-sensite aspartokinase but also those of homoserine dehydrogenase and threonine deaminase, whereas lysine repressed the aspartokinase alone. To select mutations releasing lysine-sensitive aspartokinase from feedback controls, AEC-resistant colonies were isolated from strains HNr31 and HNr53, both of which were previously found to excrete threonine on the minimal plates but not on the plates containing excess lysine. Two of 280 resistant colonies excreted large amounts of threonine. Strains AECr174 and AECr301, derived from strains HNr31 and HNr53, respectively, lacked both feedback inhibition and repression of lysine-sensitive aspartokinase. These strains produced about 7 mg of threonine per ml in the medium containing glucose and urea.